A Survey of Consumer Perceptions of Plant-Based and Clean Meat in the USA, India, and China - Bryant, Christopher; Szejda, Keri; Parekh, Nishant; Deshpande, Varun; Tse, Brian (Frontiers in Sustainable Food Systems, 2019)
Recent years have seen increasing interest in research on consumer acceptance of clean meat. Whilst some consumers are enthusiastic about the prospect of reducing the health risks, environmental harms, and animal welfare implications associated with conventional meat production, others have concerns about the product's taste, price, safety, and naturalness. Some evidence suggests that acceptance of clean meat will vary substantially across cultures, though there is currently a lack of quantitative research in Asia and country comparisons on this topic. Both are likely to be important areas given the forecasted increase in meat consumption in developing countries. Participants (n = 3.030) were recruited through the research panel CINT to take an online questionnaire about clean meat and plant-based meat. The participants were representative of China, India, and the U.S. in terms of age and gender, though participants in India and China were disproportionately urban, high income, and well-educated. As well as clean meat, participants were asked about plant-based meat, a conceptually similar product with similar potential to displace demand for conventional meat. They also answered the Meat Attachment Questionnaire and the Food Neophobia Scale. We compared these variables between countries, and used regression models to identify which demographic and attitudinal factors predicted purchase intent toward both products. We found significantly higher acceptance of clean and plant-based meat in India and China compared to the USA. We also found significantly higher food neophobia and significantly lower meat attachment in India compared to China and the USA. We identified several demographic patterns of clean and plant-based meat acceptance as well as which beliefs were important predictors of acceptance within each country. In particular, higher familiarity predicted higher acceptance of plant-based and clean meat across all countries. We found high levels of acceptance of clean meat in the three most populous countries worldwide, and with even higher levels of acceptance in China and India compared to the USA. These results underline the importance of clean meat producers exploring new markets for their products, especially as meat consumption in developing countries continues to rise.